PENGEMBANGAN APLIKASI MEDIA PEMBELAJARAN TEBAK GAMBAR FLORA DAN FAUNA BERBASIS ANDROID PADA SDN 01 TIAS BANGUN - Puspita, Dian; Ningrum, Ajeng Amelia; Muslihudin, Muhamad (STIT AL MULTAZAM, 2022)
The quick advancement of innovation in the current period of globalization has given many advantages underway in different social angles. The utilization of innovation by people in assisting with finishing work is an unquestionable requirement throughout everyday life. This innovative improvement should likewise be trailed by advancements in Human Resources (HR).Humans as technology users must be able to take advantage of current technology, as well as develop the technology in the future. How to make an android-based guessing game application, with the guessing game using the can increase the intelligence of the students of SDN 1 Tias Bangun, with the research method of observation, documentation, the Android-based Guessing Game application was built using the Embarcadero Delphi 10.4 software and using a programming language java scripts. Based on the testing of the Android-based Guess Picture application, it can be concluded that the learning media is in the form of an Android-Based Educational Game to Improve Student Learning Outcomes at SDN 1 Tias Bangun.